Application of Scrum Methodology in The Design of Micro, Small, and Medium Enterprise Systems: A Case Study on Laundry Services - Basri, Amat; Atmaja, Dewi Marini Umi; Hakim, Arif Rahman; Sanjaya, Andreas Rino (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
This study investigates the application of the Scrum methodology in developing systems for Micro, Small, and Medium Enterprises (MSMEs), specifically focusing on laundry service operations. The case study centers on D'Laundry, a laundry service provider, which has traditionally operated with conventional transaction methods. The objective of this research is to develop an MSME system employing the Scrum framework. The system analysis was executed using an Object-Oriented approach, utilizing Unified Modeling Language (UML) for modeling. The development phase employed PHP for application creation, while MySQL was used for the system database. The implementation phase was conducted within a local network, with functional system testing carried out via Black Box testing techniques. Furthermore, the software quality was assessed through a User Acceptance Test, complemented by a questionnaire-based approach. The findings offer insights into the adoption of agile methodologies by MSMEs, emphasizing digital transformation strategies.